How does morality work in the brain? A functional and structural perspective of moral behavior - Pascual, Leo; Gallardo-Pujol, David; Rodrigues, Paulo (Frontiers in Integrative Neuroscience, 2013)
Neural underpinnings of morality are not well understood yet. Researchers in moral neuroscience have tried to find specific structures and processes that shed light on how morality works. Here, we review the main brain areas that have been associated with morality at both structural and functional levels and speculate about how it can be studied. Orbital and ventromedial prefrontal cortices are implicated in emotionally-driven moral decisions, while dorsolateral prefrontal cortex seems moderate its response. These competing processes may be mediated by the anterior cingulate cortex. Parietal and temporal structures play important roles in the attribution of others' beliefs and intentions. The insular cortex is engaged during empathic processes. Other regions seem to play a more complementary role in morality. Morality is supported not by a single brain circuitry or structure, but by several circuits overlapping with other complex processes. The identification of the core features of morality and moral-related processes is needed. Neuroscience can provide meaningful insights in order to delineate the boundaries of morality in conjunction with moral psychology.